Modelling the effect of the 2018 summer heatwave and drought on isoprene emissions in a UK woodland. (22nd January 2020) - Otu‐Larbi, Frederick; Bolas, Conor G.; Ferracci, Valerio; Staniaszek, Zosia; Jones, Roderic L.; Malhi, Yadvinder; Harris, Neil R. P.; Wild, Oliver; Ashworth, Kirsti
Abstract: Projected future climatic extremes such as heatwaves and droughts are expected to have major impacts on emissions and concentrations of biogenic volatile organic compounds (bVOCs) with potential implications for air quality, climate and human health. While the effects of changing temperature and photosynthetically active radiation (PAR) on the synthesis and emission of isoprene, the most abundant of these bVOCs, are well known, the role of other environmental factors such as soil moisture stress are not fully understood and are therefore poorly represented in land surface models. As part of the Wytham Isoprene iDirac Oak Tree Measurements campaign, continuous measurements of isoprene mixing ratio were made throughout the summer of 2018 in Wytham Woods, a mixed deciduous woodland in southern England. During this time, the United Kingdom experienced a prolonged heatwave and drought, and isoprene mixing ratios were observed to increase by more than 400% at Wytham Woods under these conditions. We applied the state‐of‐the‐art FORest Canopy‐Atmosphere Transfer canopy exchange model to investigate the processes leading to these elevated concentrations. We found that although current isoprene emissions algorithms reproduced observed mixing ratios in the canopy before and after the heatwave, the model underestimated observations by 40% during the heatwave–drought period implying that models may substantially underestimate the release of isoprene to the atmosphere in future cases of mild or moderate drought. Stress‐induced emissions of isoprene based on leaf temperature and soil water content (SWC) were incorporated into current emissions algorithms leading to significant improvements in model output. A combination of SWC, leaf temperature and rewetting emission bursts provided the best model‐measurement fit with a 50% improvement compared to the baseline model. Our results highlight the need for more long‐term ecosystem‐scale observations to enable improved model representation of atmosphere–biosphere interactions in a changing global climate. Abstract : The effect of heat and drought stress, and soil rewetting on biogenic volatile organic compound emissions is poorly understood and represented in emission models. By incorporating stress‐induced emissions of isoprene, based on leaf temperature and soil moisture into a canopy exchange model, we improve model reproduction of observed isoprene mixing ratios during the 2018 heatwave–drought event that occurred in the United Kingdom.